The Changeableness of Subnational Constitutions: A Qualitative Comparative Analysis. Issue 1 (9th January 2017) - Reutter, Werner
Abstract : Why have some German Land constitutions been changed more frequently than others? This is the basic research question addressed in this article. In addition and maybe even more importantly, for the first time the article will apply fuzzy-set qualitative comparative analysis to the study of comparative constitutional policy, and thus will investigate what conditions explain the changeableness of subnational constitutions. Overall, I will argue that subnational constitutional policy is not just a manifestation of Germany's consensus democracy. On the contrary, it seems that a crucial element of majoritarian democracy – that is, a low number of effective parties – appears to be a core condition for the changeableness of constitutions. In addition, the findings suggest that any theory striving to explain the frequency and scope of constitutional amendments in a comparative perspective should include both institutional and party factors.